Check whether the following are quadratic equations:
$(x – 2) (x + 1) = (x – 1) (x + 3)$

AcademicMathematicsNCERTClass 10

Given:

Given equation is $(x – 2) (x + 1) = (x – 1) (x + 3)$

To do:

We have to check whether the given equation is quadratic.

Solution:

The standard form of a quadratic equation is $ax^2+bx+c=0$.

$(x – 2) (x + 1) = (x – 1) (x + 3)$

$x(x+1)-2(x+1)=x(x+3)-1(x+3)$

$x^2+x-2x-2=x^2+3x-x-3$

$x^2-x^2-x-2x-2+3=0$

$-3x+1=0$ is not of the form $ax^2+bx+c=0$

Therefore, $(x – 2) (x + 1) = (x – 1) (x + 3)$  is not a quadratic equation. 

raja
Updated on 10-Oct-2022 13:20:12

Advertisements